(001)‐oriented BiFeO3 films integrated on Si with enhanced electrical performances. Issue 12 (27th July 2021) - Zhang, Wei; Wu, Hao; Kang, Limin; Peng, Bowen; Bao, Jianqiu; Hu, Fangren
Abstract: Highly (001)‐oriented pure‐phase BFO films were prepared on traditional Si substrates via radio frequency magnetron sputtering (RFMS). The crystallinity of the films is found to be increased, that is, higher degree of (001) texture, larger grain size, less grain boundary, denser surface morphology, and better thickness uniformity, with increased film thickness. These factors have significant influences on the electrical properties of BFO films, that is, dielectric response, as well as ferroelectric polarization and leakage current characteristics. The 240‐nm‐thick film exhibits relatively poor electrical properties compared with other three thicker films, which is mainly due to its small grain, the enhancement of the clamping effect of neighboring grains, and the absence of domain walls. The essential roles of the evolution and distribution of grains/domains and defect charges in leakage mechanism and ferroelectric switching polarization were also investigated systematically. It was found that 600‐nm‐thick BFO film has the lowest leakage current density (as low as 1.8 × 10 −6 A / cm 2 @ 90 kV/cm) and followed a mixed SE or SCLC conduction behavior, while the leakage behavior in other films is dominated by SE and P‐F currents. All (001)‐BFO films have a giant electrical polarization which is solely originated from the contribution of ferroelectric domain switching, and it has lower switching voltage and faster switching rate in thicker films.